Persepsi Mahasiswa terhadap E-Modul Pembelajaran Mata Kuliah Fisika Atom dan Inti - Pathoni, Haerul; Jufrida, Jufrida; Saputri, Ika; Sari, Wulan (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
Based on observations in  atomic physics and nuclear learning, there are some problems see during two semester  of the course such as less using of instructional materials and instructional media  in the process of learning. In addition, content of book  used are books published in the 1990s  years and  never have been updated. The quantity of books of atomic physics and nuclear in the library is still very little. Therefore developed electronic modul (E-modul). This research used descriptif research. E-module is made using 3D software pageflip professional. E-Module has been validated by experts for media and content of  e-module. The result was perception of students on average 83.5% on core structure module and 89 % on radioactivity module with very good category.